Reducing Misconceptions of Elementary School Students Through Guided Inquiry Learning - I Gede Margunayasa; Nyoman Dantes; . A. I. N. Marhaeni; I Wayan Suastra (Universitas Pendidikan Ganesha, 2021)
Some students have a conception of the concepts before they attend school lessons. It is because students are interested in the learning material delivered by the teacher. This study aimed to analyze the effect of the guided inquiry learning model on the misconceptions of fifth graders in elementary schools. This type of research is quasi-experimental research. The population of this study amounted to 43 students in elementary schools. The research sample was selected using multistage random sampling. The instrument used to collect data is a questionnaire. The technique used to collect data is descriptive qualitative, and quantitative. The study results showed significant differences in students' misconceptions between groups of students who were taught with guided inquiry learning and conventional learning (F = 7,447; p<0,05). Misconceptions in students who learn with guided inquiry learning are lower than students who learn with conventional learning. This research implies that guided inquiry learning can be used by teachers in learning to overcome misconceptions in students.